2015
DOI: 10.1016/j.jcis.2015.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles decorated anatase TiO 2 nanotubes for removal of pentachlorophenol from water

Abstract: a b s t r a c tOne-dimensional nanotubes are promising materials for environmental applications. In this study, anatase TiO 2 nanotubes (TNTs) were fabricated using an alkaline hydrothermal method at 130°C and then calcinated at 400°C for 2 h. Ag nanoparticles were photo-deposited onto the TNTs for enhanced photodegradation of pentachlorophenol (PCP) under simulated solar light. The samples were characterized using transmission electron microscopy, physical adsorption of nitrogen, X-ray diffraction, X-ray phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…PCP has accumulated in the environment, thereby causing a potential risk to animals and humans (Kondo et al, 2005;Maenpaa et al, 2004;Yu et al, 2015). Halogenated phenolic compounds, including PCP, can accumulate in the blood and fetal tissues of birds, fish, cetaceans, and other mammals (Kunisue and Tanabe, 2009;Montano et al, 2013), and has also been found in bird eggs (Berger et al, 2004;Brambilla et al, 2009;Maenpaa et al, 2004).…”
Section: Pcp Content In Tissues Of L Striatamentioning
confidence: 99%
“…PCP has accumulated in the environment, thereby causing a potential risk to animals and humans (Kondo et al, 2005;Maenpaa et al, 2004;Yu et al, 2015). Halogenated phenolic compounds, including PCP, can accumulate in the blood and fetal tissues of birds, fish, cetaceans, and other mammals (Kunisue and Tanabe, 2009;Montano et al, 2013), and has also been found in bird eggs (Berger et al, 2004;Brambilla et al, 2009;Maenpaa et al, 2004).…”
Section: Pcp Content In Tissues Of L Striatamentioning
confidence: 99%
“…Moreover, the film is coated on the substrate having amorphous structure that affected the intensity of the diffraction peaks of TNTs. In the XPS analysis results of the O1s in Ag/TNTs, there is a major peak at 531 eV with binding energy characterising for oxygen in TiO 2 and a smaller peak at 528 eV associated with characteristic for O ¡ [31]. The bonding of Ag into TNTs was investigated by the high-resolution XPS of the Ag 3d.…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 99%
“…The results of the Ag3d XPS ( Figure 5(d)) have the following spotlight: first, the sample had more common smaller peaks inside the two top large spectra. After using Gaussian fit to analyse the XPS spectra of Ag 3d, there is appearance of peaks at 367.5, 368.6, 371.8, and 375 eV with binding energy positions corresponding to Ag + 3d 5/2 , Ag 0 3d 5/2 , Ag + 3d 3/2 and Ag 0 3d 3/2 , respectively [16,31]. This shows that there is an existence of two states of silver including Ag + and Ag 0 .…”
Section: X-ray Diffraction Pattern Analysismentioning
confidence: 99%
“…Pentachlorophenol (PCP) is a highly toxic persistent organic pollutant present in the environment due to its extensive use as a pesticide in agriculture and in wood preservation in industries. Its presence in water and soil could also contaminate the groundwater and become a potential risk to humans and animals [1].…”
Section: Introductionmentioning
confidence: 99%